Legal Policy on the National Education System In Influencing Worker Productivity in Indonesia - Aji, Rizqon Halal Syah; Syaukani, Mohd Nasir Mohd; Panjaitan, Mangasi; Rezki, Annissa (Jurnal Cita Hukum, 2022)
Human resource investment significantly impacts the economic growth and development of a nation, including Indonesia. It is believed that education expenditures affect worker productivity in Indonesia. Theoretically, education expenditures will contribute to an improvement in worker productivity. Several factors, including a comparison of the competitiveness of domestic workers to the competitiveness of international workers, can be used to determine the effect of education investment on the rise in worker productivity. Empirically, productivity is a function of worker skills. The quantity of a worker's salary might be used to gauge their competitiveness and productivity. At the national level, it is simple to identify the productivity of various economic sectors, such as agriculture, services, and manufacturing. Due to the lack of trained people required by the labour market, conditions in Indonesia have prevented the three sectors mentioned above from achieving their full potential for productivity growth. This condition directly manifests some concerns, notably Indonesia's investment in education and worker productivity, which impacts economic growth. This study employs qualitative research methodologies of the normative research type. This study's research objectives will be satisfied by the study model. This study will answer how education investment affects worker productivity in Indonesia. The study's findings indicate that it is not accurate to assert that the education policy in Indonesia has a good effect on enhancing workers' abilities. Therefore, the issue of worker productivity must still be handled seriously to compete with workers from other nations.